To Compare the Efficacy of Nifedipine and Tamsulosin 0.4 mg in Expulsion of Lower Ureteric Stones - Mhammad Zahid Ahmed, Nauman Ahmed, Muhammad Asif, Muhammad Waqar Shahid, Aftab Ahmed Channa, Naeem Ahmed Cheema (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the effectiveness of nifedipine and tamsulosin for expulsion lower ureteral stones with size ranging from 4mm-11mm. Study Design: A Randomized controlled trial. Methods: The study was held over a 2-year duration from January 2018 to December 2019 in the Urology department of Islam Medical College/ Teaching hospital Sialkot and Govt. Kot Khawaja Saeed Teaching Hospital Lahore. 72 total patients, 37 patients in each group, were selected for the study. The patients in A group were treated with alpha-1-blocker alone (tamsulosin), patients in B group were treated with calcium channel blockers (nifedipine 30-mg). Data on stone size, transit time, stone removal rate and control of pain were analyzed and collected. The mean ± SD of continuous variables was used to determine the percentage and frequency of categorical variables. The student’s t-test and Chi-square test were applied to compare numerical and categorical variables, correspondingly. Results: 72 total patients were involved and 36 patients in each group were analyzed after randomization. The patients mean age in A group was 36.40 ± 6.98 years, and in B group it was 38.01 ± 9.40 years correspondingly (p 0.76). The mean size of stone was 6.40 ± 1.82 mm in group A and in group B it was 6.51 ± 1.69 mm (p 0.80). Mean time of expulsion in A group was 8.40 ± 2.41 days and for group B; it was 6.71 ± 2.33 days (p <0.001). Patients receiving tamsulosin endured suggestively fewer attacks of pain related with patients receiving nifedipine treatment (p 0.017). Conclusion: The tamsulosin is safe treatment for appropriately sized lower ureteral stones as compared to nifedipine. The tamsulosin monotherapy have clear advantage over nifedipine but more detailed school studies are needed for efficacy and safety.